2022
DOI: 10.1097/md.0000000000030106
|View full text |Cite
|
Sign up to set email alerts
|

Protected carotid artery stenting in patients with severe stenosis

Abstract: Intraplaque hemorrhage (IPH) and ulcers are the major findings of unstable plaques. In addition, initial symptoms are associated with postprocedural complications after carotid artery stenting (CAS). The aim of this study was to determine the safety of CAS using an embolic protection device in symptomatic patients with severe carotid artery stenosis and unstable plaques such as IPH and ulcers. This retrospective study included 140 consecutive patients with severe carotid stenosis. These patients underwent prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Because the frequency of NIILs between the IPH positive and IPH negative groups did not appear to differ significantly, an earlier investigation discovered that IPH detected by magnetization prepared rapid gradient echo (MPRAGE) was not a major risk factor for cerebral embolism following CAS (21). In a subsequent investigation using high-resolution magnetic resonance imaging (HR-MRI), similar outcomes that demonstrated the security of protected CAS in individuals with IPH and ulceration were revealed (22). We speculate that these findings may be due to the fact that they did not quantify the volume of IPH.…”
Section: Discussionmentioning
confidence: 99%
“…Because the frequency of NIILs between the IPH positive and IPH negative groups did not appear to differ significantly, an earlier investigation discovered that IPH detected by magnetization prepared rapid gradient echo (MPRAGE) was not a major risk factor for cerebral embolism following CAS (21). In a subsequent investigation using high-resolution magnetic resonance imaging (HR-MRI), similar outcomes that demonstrated the security of protected CAS in individuals with IPH and ulceration were revealed (22). We speculate that these findings may be due to the fact that they did not quantify the volume of IPH.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the intraoperative use of cerebral umbrella, perioperative use of antiplatelet aggregation drugs, and no balloon dilation after stent implantation, there was still one patient with acute ischemic stroke aggravation after surgery, and no signi cant large vessel occlusion was found in reexamination of the angiography, which was considered as perforator artery occlusion. The use of cerebral umbrella can effectively reduce the occurrence of cerebral infarction after CAS surgery [22,23], but there is no consensus on whether tiro ban and other antiplatelet drugs should be routinely used [24]. Perhaps preoperative cervical vascular color ultrasound and magnetic resonance vascular plaque imaging should be used to determine whether it is vulnerable plaque, in order to conduct targeted preventive treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported that IPH is not a significant risk factor for cerebral embolism during protected carotid artery stent placement in patients with severe carotid stenosis [ 6 , 12 ]. Plaque ulceration is not a significant risk factor for cerebral embolism after CAS [ 24 ]. In our study, risk factors of post-procedural events after CAS were analyzed, including unstable findings (such as IPH, LRNC, thin or ruptured fibrous cap on carotid VWI), intraluminal thrombus, degree of stenosis, ICA flow delay, and flow arrest during CAS on carotid angiography.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 Plaque ulceration is not a significant risk factor for cerebral embolism after CAS. 24 In our study, risk factors of post-procedural events after CAS were analyzed, including unstable findings (such as IPH, LRNC, thin or ruptured fibrous cap on carotid VWI), intraluminal thrombus, degree of stenosis, ICA flow delay, and flow arrest during CAS on carotid angiography. Our results correlated with those of studies suggesting that unstable plaque findings on carotid VWI were not associated with post-procedural clinical events.…”
Section: Discussionmentioning
confidence: 99%